EXAMINATION OF PHYTOCHEMICAL CONSTITUENTS – USING SEED EXTRACT OF MADHUCA LONGIFOLIA - D, MANIKANDAN; S, PARVEEN; PA, PERIASAMY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Our main scope and objective are to prepare seed extract of Madhuca longifolia, to characterize them using phytochemical activity studies, and to study the presence of so many bioactive substances established phytochemical activity and anti-foot ulcer treatment. Methods: Weighed 75 g of plant sample (without preliminary drying) accurately (precisely weighed to within 0.10 g) in a tarred evaporating dish. Care was taken so that no substantial amount of moisture is lost during preparation and that was representative of the official sample and the sample has been made to screening to following studies such as physicochemical constants, determination of moisture content, evaluation of pH of aqueous solution, evaluation of total ash, evaluation of acid-insoluble ash, evaluation of extractive values, evaluation of water-soluble extractive, evaluation of alcohol-soluble extractive, and preliminary phytochemical screening phytochemical profile of M. longifolia seed. Results: The presence of so many bioactive substances established phytochemical activity and anti-foot ulcer treatment using M. longifolia seed which supports the traditional tribal medicinal consumption of the plant. Conclusion: The quality of the plant can be estimated by determining the physical parameters. These investigations are of great importance for carrying out the revalidation and it was accomplished from the phytochemical study that the solvent extract contains flavonoid, carbohydrate, saponin, tannin, glycoside, protein, alkaloid, and amino acid which are responsible for various pharmacological actions and promotes that biological study is required to explore their potential therapeutic activities.